2014
DOI: 10.1167/iovs.14-14598
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell-Inner Plexiform Layer Thickness of High Definition Optical Coherence Tomography in Perimetric and Preperimetric Glaucoma

Abstract: The diagnostic ability of GCIPL parameters was similar to that of ONH and peripapillary RNFL parameters in perimetric glaucoma. However, in preperimetric glaucoma, the diagnostic ability of GCIPL parameters was significantly lower than that of ONH and RNFL parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 38 publications
(48 reference statements)
0
48
1
3
Order By: Relevance
“…RNFL thickness measurements were performed with Cirrus HD-OCT (software V.7.0.1.290) using the Optic Disc Cube 200×200 protocol 15 16. The 12 clock-hour RNFL thickness measurements (in the right eye format) were grouped to closely match the sectors of the OCTA parameters.…”
Section: Methodsmentioning
confidence: 99%
“…RNFL thickness measurements were performed with Cirrus HD-OCT (software V.7.0.1.290) using the Optic Disc Cube 200×200 protocol 15 16. The 12 clock-hour RNFL thickness measurements (in the right eye format) were grouped to closely match the sectors of the OCTA parameters.…”
Section: Methodsmentioning
confidence: 99%
“…2 Recent studies showed that the ability of the macular GCIPL parameters to diagnose glaucoma is comparable with that of the peripapillaryretinal nerve fiber layer (pRNFL) and optic nerve head parameters. [3][4][5][6][7][8] Because of the characteristic distribution of the retinal nerve fiber axons in the retina, asymmetric visual field defects often occur between the superior and inferior hemifields. Mikelberg and Drance 9 found that 70% of eyes had initial damage limited to a single hemifield and 57% still had only a single hemifield defect at the completion of follow-up.…”
mentioning
confidence: 99%
“…Care should therefore be taken when interpreting the results of studies where OCT has been evaluated outside of this context. In fact, most studies examining the diagnostic ability of OCT in glaucoma have included patients with established visual field defects and relatively few have examined the utility of imaging specifically in early disease (Begum et al, 2014;Jeoung et al, 2014;Lisboa et al, 2012Lisboa et al, , 2013bSung et al, 2012;Takayama et al, 2012;Wu et al, 2012).…”
Section: Detecting Structural Changementioning
confidence: 99%
“…A growing number of other studies have examined the diagnostic ability of macular measures in early glaucoma, including in eyes without defects on conventional perimetry (Begum et al, 2014;Jeoung et al, 2013;Lisboa et al, 2013b;Takayama et al, 2012). Begum and colleagues compared 53 healthy eyes to 83 glaucomatous eyes, including 21 with preperimetric glaucoma (Begum et al, 2014).…”
Section: Imaging the Maculamentioning
confidence: 99%
See 1 more Smart Citation